KUALITAS PELAYANAN PETUGAS PENDAFTARAN RAWAT JALAN TERHADAP PELAYANAN PRIMA DI RUMAH SAKIT: STUDI LITERATUR - Yanasta Yudo Pratama; Sri Wahyunita Mohamad; Tri Ani Marwati; Muhammad Syamsu Hidayat (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2022)
The Outpatient Registration Center is a leading service unit which is one part of the medical record task and the place where the patient first meets the officer. Excellent Service, namely the best service provided in accordance with expectations or even exceeding customer expectations. Assessment of service quality through 5 dimensions, namely Ability, Attitude, Attention, Action, and Responsibility. To determine the factors related to the registration service officer of the excellent service in the hospital. Literature search reviewed using the Google Scholar Database with the topic "Quality of Outpatient Registration Officer Service Against Excellent Service" Search keywords used in the database are Keyword and Boolean operators which are used to expand or specify the search so that it can make it easier to determine articles or research journals used. Literature search aims to get as many scientific publications on a given topic as possible by taking into account the interrelationships between keywords so that there are 7 suitable studies. The results of the literature reviewed show that the Service Quality of Registration Officers for Excellent Service in Hospitals There is a relationship between them, namely Ability, Attitude, Attention, Action, and Responsibility. Of the five dimensions of Excellent Service to the service quality of the registration officer, most of them have shown the results of the service quality assessment which are considered good and have achieved minimal service standards. Based on the results of the 7 Literature Studies that have been found by the author on the Dimensions of Attitude, Attention, Action, Ability, Appearance and Responsibility for Excellent Service in Hospitals There is a Meaningful Relationship because of the 6 Dimensions of Excellent Service it is very important for a service quality in the hospital